2015
DOI: 10.1371/journal.pone.0140587
|View full text |Cite|
|
Sign up to set email alerts
|

Computational Characterization of Exogenous MicroRNAs that Can Be Transferred into Human Circulation

Abstract: MicroRNAs have been long considered synthesized endogenously until very recent discoveries showing that human can absorb dietary microRNAs from animal and plant origins while the mechanism remains unknown. Compelling evidences of microRNAs from rice, milk, and honeysuckle transported to human blood and tissues have created a high volume of interests in the fundamental questions that which and how exogenous microRNAs can be transferred into human circulation and possibly exert functions in humans. Here we prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 61 publications
(72 reference statements)
2
51
0
Order By: Relevance
“…The majority of milk microRNAs are encapsulated within EVs that ensure their stability against harsh conditions (Benmoussa et al., , ; van Herwijnen et al., ; Wang, ). Milk microRNAs can be specifically loaded into different kinds of EVs (Shu, Chiang, Zempleni, & Cui, ; Villarroya‐Beltri et al., ), leading to specific microRNA profiles between EV subsets (Benmoussa et al., ; Chiang, Shu, Zempleni, & Cui, ; Manca et al., ; Shu et al., ), and this loading process can be influenced by the environment, by dietary habits (Paredes et al., ; Xi et al., ) or food supplementation as observed for dietary ginseng polysaccharide supplementation on porcine milk microRNAs (Sun et al., ).…”
Section: Milk Micrornas In Health and Diseasementioning
confidence: 99%
“…The majority of milk microRNAs are encapsulated within EVs that ensure their stability against harsh conditions (Benmoussa et al., , ; van Herwijnen et al., ; Wang, ). Milk microRNAs can be specifically loaded into different kinds of EVs (Shu, Chiang, Zempleni, & Cui, ; Villarroya‐Beltri et al., ), leading to specific microRNA profiles between EV subsets (Benmoussa et al., ; Chiang, Shu, Zempleni, & Cui, ; Manca et al., ; Shu et al., ), and this loading process can be influenced by the environment, by dietary habits (Paredes et al., ; Xi et al., ) or food supplementation as observed for dietary ginseng polysaccharide supplementation on porcine milk microRNAs (Sun et al., ).…”
Section: Milk Micrornas In Health and Diseasementioning
confidence: 99%
“…Exosomes accumulate in immune 56 cells if transferred across species boundaries (6)(7)(8). We further demonstrated that bovine milk 57 exosomes contribute to the body pool of microRNAs in human milk feeding and murine 58 exosome depletion studies (6,9,10). MicroRNAs in dietary exosomes alter gene expression 59 across species boundaries (6,11).…”
mentioning
confidence: 82%
“…Shu et al (2015) used bioinformatics tools to characterize the structural characteristics of exogenous miRNAs that can contribute to cross-species transportation and thus be transferred into human circulation . Of note is that exogenous miRNAs (xenomiRs) were only found in 17% of the tissue samples (from 392 total samples), with several studies being completely void of any xenomiRs.…”
Section: The Landscape Of Exogenous Ncrnas In Biological Fluids and Tmentioning
confidence: 99%